Endemic Melioidosis in Residents of Desert Region after Atypically Intense Rainfall in Central Australia, 2011 - Teem-Wing Yip; Saliya Hewagama; Mark Mayo; Erin P. Price; Derek Sarovich; Ivan Bastian; Robert W. Baird; Brian G. Spratt; Bart J. Currie (Emerging Infectious Diseases, 2015)
After heavy rains and flooding during early 2011 in the normally arid interior of Australia, melioidosis was diagnosed in 6 persons over a 4-month period. Although the precise global distribution of the causal bacterium Burkholderia pseudomallei remains to be determined, this organism can clearly survive in harsh and even desert environments outside the wet tropics.